Non-invasive dry electrodes for EEG - Silva, M. F. (2010)
This paper presents a non-invasive dry electrode for electroencephalogram (EEG) acquisition. These electrodes can be integrated in a wearable braincap for wireless EEG that can be used for a long time by patients avoiding the contact gel. This wearable braincap will allow mobility to the patients, while simultaneously having their electrical brain activity monitored. The fabricated dry electrodes are based on iridium oxide (IrOx) deposited by reactively pulsed sputtering. The electrode employs an array of microtips that penetrate the outer skin layer (i.e. stratum corneum) that is 10 µm thick. The microtips (100-200 µm deep) were micromachined through a bulk-micromachining process based on a KOH solution.